Microsatellite variation revealed panmictic pattern for Triatoma brasiliensis (Triatominae: Reduviidae) in rural northeastern Brazil: The control measures implications - Mendonça Bezerra, Claudia (2020)
Background Triatoma brasiliensis Neiva, 1911 is the main vector of Trypanosoma cruzi in the caatinga of Northeastern Brazil. Despite of its epidemiological relevance, there are few studies on its genetic variability. Using microsatellite markers, we characterized the variability and dynamics of infestation and reinfestation of T. brasiliensis after residual insecticide spraying in five surveys conducted in a well-defined rural area located in the municipality of Tauá, Ceará, between 2009 and 2015. We evaluated: (1) general variability among local of captures; (2) variability along the time analysis (2009, 2010 and 2015); (3) and reinfestation process. Results On the analysis (1) global and pairwise FST values suggested absence of clusters among the area. AMOVA indicated that total variation is mainly represented by individual differences. Absence of clustering indicates a panmitic unit, with free gene flow. For (2), Pairwise FST indicated alterations in the genetic profile of the triatomines along the time. (3) Analysis of the reinfestation process showed that the domiciliary units investigated had different sources of infestation despite of its proximity. Conclusions Observed homogeneity can be explained by the great dispersal capacity of T. brasiliensis, overlapping the different environments. Persistent house infestation in Tauá may be attributed to the occurrence of postspraying residual foci and the invasion of triatomines from their natural habitats.